Strategy for the successful implementation of ERP systems in Zimbabwe - Gobvu, Tanatsiwa (Midlands State University, 2020)
Modern-day businesses have come to realise the importance of collaborating business processes and functional areas within an organisation. Enterprising Resource Planning (ERP) systems have been developed to fulfil that role - seamless integration of functional areas and business processes across departments of an organisation. In-line with understanding the indispensability of ERP systems, this study was dedicated to developing a strategy for the implementation of SAP ERP system in the context of State Owned Enterprises (SOEs) in Zimbabwe. Data was collected from ICT specialists and SAP users in the SOEs that have implemented SAP in Zimbabwe, ICT projects managers from both the SOEs and SAP implementing vendors or consultants. Quantitative data for the study was extracted from 66 SOEs’ employees (including ICT specialist, ICT project managers and super user) drawn from 15 sampled SOEs. Qualitative data was collected from 9 ICT project projects managers drawn from the SAP implementing companies. This therefore means that this study was both quantitative and qualitative premised on the pragmatist philosophy. The inductive approach was employed to ensure that the proposed ERP implementation strategy is developed after collecting empirical primary data. A basic descriptive survey design was employed in which questionnaires were distributed to SOEs employees. Interviews were applied for collecting data from the SAP implementing consultants. The quantitative data was analysed using SPSS version 20 and Microsoft Excel 2010 to summarise the statistical results in the form of tables, pie charts and bar graphs. Thematic analysis approach was applied to analyse the qualitative data. The collected empirical qualitative data was also used as corroborating evidence to the quantitative analysis results in the form of verbatim quotes extracted from the key informants.